A matéria do nada: potências, flutuações, e experiência no nada poético de Carlos Drumond Andrade - Corrêa, Danilo Barcelos (2011)
Carlos Drummond de Andrade, in his poems, reflects aesthetically about the self, time and language, silencing his readers so power over nothing acts on them. To think about nothingness s matter in the poet s poems is treading a path in his thinking, feeling poetically as he shows, "the power of speech and silence" of his verses creating the self. Analyzing his poems as the poet reflects on the twentieth century and its major problems, in tune with the different disciplines of knowledge and central issues of that time period. By checking this it is understood how the poet conceives the concepts of poem, poetry, time and silence. Establishing these points it becomes possible to see how poems effect and suspend the self in nothingness, unmaking and remaking the self in the poetic thought of Drummond.